Forming a Definition of a Town. Poland in the Context of Universal History - Marek Słoń (Przegląd Nauk Historycznych)
In the light of the current state of research, it does not seem possible to create a universal definition of town, covering all eras and cultures. However, if the field of analysis is narrowed, it becomes possible and desirable. As part of the work on ontological foundations of geographic information systems for the history of Poland, a tool has been developed to distinguish between basic (villages) and higher (towns) units of the settlement network. Three basic criteria are assessed: whether a settlement was considered a town by its contemporaries, whether it was large and complex compared to a village, and whether it had the legal status of a town. In different periods and legal systems, each of these criteria may have had different meanings, and the combined consideration of all three allows for the classification of doubtful cases. The second part of the article predicates the application of such a definition in the analysis of the urban network of twelve counties (within their contemporary boundaries) in four time sections: 1200, 1600, 1900 and 1939. Boundary situations included primarily early Piast townships with different functions, followed by agglomerations consisting of more than one urban commune in 1600 and, finally, so-called ‘urban settlements’ in the Congress Kingdom in 1900. The article also determines the number of towns in a given area at the indicated point in time. It seems particularly important to have an unambiguous and consistent classification of settlement units for a long period and a relatively large area, particularly in view of the creation of historical geoportals.